Development of a combined canine distemper virus specific RT-PCR protocol for the differentiation of infected and vaccinated animals (DIVA) and genetic characterization of the hemagglutinin gene of seven Chinese strains demonstrated in dogs - Yi, Li (J Virol Methods, 2012)
A combined reverse-transcription polymerase chain reaction (RT-PCR) method was developed for the detection and differentiation of wild-type and vaccine strains of the canine distemper virus (CDV). A pair of primers (P1/P2) was used to detect both CDV wild-type strains and vaccines. Another pair (P3/P4) was used to detect only CDV wild-type strains. A 335 bp fragment was amplified from the genomic RNA of the vaccine and wild-type strains. A 555 bp fragment was amplified specifically from the genomic RNA of the wild-type strains. No amplification was achieved for the uninfected cells, cells infected with canine parvovirus, canine coronavirus, or canine adenovirus. The combined RT-PCR method detected effectively and differentiated the CDV wild-type and vaccine strains by two separate RT-PCRs. The method can be used for clinical detection and epidemiological surveillance. The phylogenetic analysis of the hemagglutinin gene of the local wild-type CDV strains revealed that the seven local isolates all belonged to the Asia-1 lineage, and were clustered closely with one another at the same location. These results suggested that the CDV genotype Asia-1 is circulating currently in domestic dogs in China.